Analisis Putusan Pemerkosaan yang Dilakukan oleh Anggota Militer Berdasarkan Hasil Visum Et Repertum Nomor : VER/41/KES.15./XII/2018 - Karina Elintra Kloko; Indra Koswara (Universitas Medan Area, 2023)
Visum Et Repertum or VeR is an official written statement made by a doctor for the needs of investigators regarding medical. One type of crime that requires a Ver outcome is rape. Military members who have cases will be tried in military courts as regulated in Law No. 31 of 1997 concerning military courts. The purpose of this research is to find out the results of the Visum Et Repertum (VeR) can be used as evidence in investigating rape cases and whether the legal decision in this case is influenced by the results of the Visum Et Repertum (VeR). This research method uses normative juridical analysis techniques and literature. The results found are evidence of the elements of the crime of rape from the results of the examination contained in the visum et repertum, determining the steps taken by the Police in investigating a rape case. Visum Et Repertum clearly influences the judge's decision because it explains as clearly as possible what happened at the time of the incident with evidence in the post mortem et refertum. Based on the results of the Visum Et Repertum and the testimony of other witnesses, the defendant was sentenced to 10 (ten) months in prison and court costs to the defendant in the amount of Rp. 5,000.00 (five thousand rupiah) on charges of rape and the second charge of intentionally and openly violating decency. Having Ver evidence in the rape case sheds light on what happened during the incident and clarifies the testimony of witnesses.